The Win–Win Effects of an Invasive Plant Biochar on a Soil–Crop System: Controlling a Bacterial Soilborne Disease and Stabilizing the Soil Microbial Community Network - Sheng Wang; Lei Wang; Sicong Li; Tiantian Zhang; Kunzheng Cai (Microorganisms, 2024)
Biochar is increasingly being recognized as an effective soil amendment to enhance plant health and improve soil quality, but the complex relationships among biochar, plant resistance, and the soil microbial community are not clear. In this study, biochar derived from an invasive plant (Solidago canadensis L.) was used to investigate its impacts on bacterial wilt control, soil quality, and microbial regulation. The results reveal that the invasive plant biochar application significantly reduced the abundance of Ralstonia solanacearum in the soil (16.8–32.9%) and wilt disease index (14.0–49.2%) and promoted tomato growth. The biochar treatment increased the soil organic carbon, nutrient availability, soil chitinase, and sucrase activities under pathogen inoculation. The biochar did not influence the soil bacterial community diversity, but significantly increased the relative abundance of beneficial organisms, such as Bacillus and Sphingomonas. Biochar application increased the number of nodes, edges, and the average degree of soil microbial symbiotic network, thereby enhancing the stability and complexity of the bacterial community. These findings suggest that the invasive plant biochar produces win–win effects on plant–soil systems by suppressing soilborne wilt disease, enhancing the stability of the soil microbial community network, and promoting resource utilization, indicating its good potential in sustainable soil management.